Design and development of modified high efficient high gain DC-DC converter for SPV standalone systems - Kariyat, Vineeth Kumar Pothera; Janardhanan, Jijesh Jisha (Institute of Advanced Engineering and Science, 2023)
A conventional DC-DC converter is not viable for power conditioning in standalone solar photovoltaic applications. Switching losses are the primary reason for the poor performance of conventional DC-DC converters. To mitigate the issues in conventional DC-DC converters, a high efficient high gain (HEHG) DC-DC converter is designed and developed in this research work. Modified HEHG converter utilizes the passive components switched capacitors, coupled inductor, and resistor capacitor (RC) snubber circuit for minimizing the switching losses and improving the overall power conversion efficiency of the solar photovoltaic (SPV) system. In addition, a modified D-sweep maximum power point tracking (MPPT) algorithm is in-corporate into this system to improve the tracking efficiency of the SPV system. HEHG for a standalone system is designed using MATLAB/Simulink environment and developed the hard-ware prototype. As a part of the validation, real-time testing is carried out and compares the performance of the HEHG converter with a traditional DC-DC converter. The theoretical efficiency of the HEHG converter is 96.01%, and the real-time efficiency is 95.62%. Found that theoretical and practical values of performance parameters are closely tallying.